2019
DOI: 10.1111/aor.13507
|View full text |Cite
|
Sign up to set email alerts
|

New versatile dual‐support pediatric heart pump

Abstract: Mechanical circulatory support (MCS) devices for pediatric patients continue to lag in development behind those for adults. There is no heart pump with the design innovation to support dysfunctional states of heart failure and the anatomic heterogeneity of cardiac defects in pediatric patients. To address this unmet need, we are developing a versatile MCS technology with 2 separate blood pumps under 1 housing, whereby a centrifugal pump rotates around an axial pump. In this study, we advanced the design with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…Historically, large-scale centrifugal pumps were designed to recirculate and oxygenate water for fish and live bait on a fishing boat, similar to the purpose of media perfusion on a microfluidic device. 40 This design and related waterwheel-based systems have been integrated into smaller-scale pumps for use as an artificial heart pump 41 as well as in microfluidic technology. 27,28,30,[42][43][44] To adapt the centrifugal pump design to be compatible with recirculating fluid flow in a microfluidic device, spinning magnets were used to drive impeller rotation.…”
Section: Concept Of the Microscale Impeller Pumpmentioning
confidence: 99%
“…Historically, large-scale centrifugal pumps were designed to recirculate and oxygenate water for fish and live bait on a fishing boat, similar to the purpose of media perfusion on a microfluidic device. 40 This design and related waterwheel-based systems have been integrated into smaller-scale pumps for use as an artificial heart pump 41 as well as in microfluidic technology. 27,28,30,[42][43][44] To adapt the centrifugal pump design to be compatible with recirculating fluid flow in a microfluidic device, spinning magnets were used to drive impeller rotation.…”
Section: Concept Of the Microscale Impeller Pumpmentioning
confidence: 99%
“…Carson Fox et al of Drexel University, Philadelphia, PA, USA reported on their development of a pediatric MCS incorporating 2 separate pumps in a single housing whereby a centrifugal pump rotates around an axial pump. The axial pump generated pressure rises of 1‐112 mm Hg for 2‐5 L/min at 10 000‐14 000 rpm, and the centrifugal pump produced pressure rises of 1‐184 mm Hg for 2‐5 L/min at 1750‐3000 rpm.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%
“…Over the past decade, researchers, clinicians, and organizations have devoted appreciable effort to raise awareness about the significant need for investment in pediatric treatment strategies, medical devices, and technologies 5,10‐14 . They seek to identify barriers in the development of new pediatric therapies and to devise novel solution strategies for improving access to life‐saving medical products for pediatric patients, including artificial organs and related technology.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9] Over the past decade, researchers, clinicians, and organizations have devoted appreciable effort to raise awareness about the significant need for investment in pediatric treatment strategies, medical devices, and technologies. 5,[10][11][12][13][14] They seek to identify barriers in the development of new pediatric therapies and to devise novel solution strategies for improving access to life-saving medical products for pediatric patients, including artificial organs and related technology. Human-centered design of medical devices that meet the evolving pediatric patient where they are in growth and development is of great importance to facilitate the health and well-being of the next generation.…”
Section: Introductionmentioning
confidence: 99%